2021
DOI: 10.1021/acs.iecr.1c01526
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Central Jet and Annular Sheet Atomizers at Identical Gas Momentum Flows

Abstract: This study compares three different nozzle flow configurationscentral liquid jet with surrounding gas phase, liquid sheet with central gas phase, and liquid sheet with inner and outer gas phases. To guarantee constant velocities, as well as momentum flows at the nozzle orifice, a nozzle with identical orifice areas (a central tube with inner and outer slits) was utilized in the experiments. The influence of gas velocity (GLR), dynamic viscosity of the liquid, and nozzle configuration on the resulting droplet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To date, there is no unified theory of gas atomization of liquids, especially in the case of rheologically complex systems. Therefore, the study of the atomization processes of such liquids containing gases is one of the key factors in developing the annular nozzle-ejector intended for various purposes [41][42][43][44]. One of the research fields is the optimization of the ANAE efficiency under the influence of structural and operational parameters.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there is no unified theory of gas atomization of liquids, especially in the case of rheologically complex systems. Therefore, the study of the atomization processes of such liquids containing gases is one of the key factors in developing the annular nozzle-ejector intended for various purposes [41][42][43][44]. One of the research fields is the optimization of the ANAE efficiency under the influence of structural and operational parameters.…”
Section: Resultsmentioning
confidence: 99%
“…As the experiments were carried out over a wide range of liquid mass flows ( Ṁliq = 20-500 kg•h −1 ), two different spray test rigs were employed. The ATMOspheric spray test rig (ATMO), which is described in detail in Wachter et al [38], was utilized for liquid mass flows at the lab-scale between Ṁliq = 20-100 kg•h −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The above studies deal with the liquid jet interaction with the high-speed air stream. However, it was shown that sheet atomization is more effective than a liquid jet in obtaining finer atomization (Wachter et al 9 ). Lately, shock wave-liquid sheet interaction studies (Jeon et al 10 ) revealed that the thicker viscous sheet attenuates the shock strength due to the energy absorption.…”
Section: Introductionmentioning
confidence: 99%